Finding the common ground: Teachers' and employers' representations of English in an assessment context. (7th April 2015) - Child, Simon; Johnson, Martin; Mehta, Sanjana; Charles, Annabel
Abstract There has been a long‐standing debate about how 'English' can be defined. Educational policy changes have typically been driven by differing representations of the subject, and have ranged from broad 'aesthetic' definitions to more narrow 'functional' views. The present study aims to analyse areas of consensus and contention in stakeholders' discourse regarding English. A questionnaire‐based survey and focus groups were used to explore how teachers and employers viewed English as a subject. Their views were conceptualised into three themes: the importance of functional English; English as atomistic versus holistic study; and English as critical thought. These themes are discussed in relation to historical definitions of 'English', and their implications for the future reform of English qualifications.